Audit Opinion and Fraud in Local Government: Case of Indonesia - Hikam, Saeful; Yunieta, Yunieta; Rizkarmen, Muhammad (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
This paper aims to examine the relationship between government audit opinion and fraud in local government in Indonesia. We utilize logistic regression analysis to test the hypothesis using a sample of 28 local governments in West Java province in periods of the fiscal year 2012 to 2017. This study finds that audit opinion significantly affects the fraud. There is a strong relationship between audit opinion and fraud. Moreover, the unqualified opinion awarded by The Audit Board of the Republic of Indonesia (BPK RI) to local government represented the real condition of local governments in their good governance and accountability. This finding is also robust when we measure fraud by other proxies namely penalty and state-loss. This study provides a useful suggestion for state audit institution namely BPK RI regarding the importance of regular government auditing. Follow-up the audit recommendations play an important role in improving internal control effectiveness, accountability, governance, and transparency. This improvement will reduce the level of fraud in local governments. This study not only fills the gap of few literature on how to reduce fraud by considering the role of auditing but also measures the important role of government auditing in reducing and preventing fraud.